2019
DOI: 10.15537/smj.2019.11.24654
|View full text |Cite
|
Sign up to set email alerts
|

Illness anxiety disorder and perception of disease and distress among medical students in western Saudi Arabia

Abstract: Objectives: To estimate and assess the prevalence and predictors of illness anxiety disorder among Saudi medical students in western Saudi Arabia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
15
2
Order By: Relevance
“…30 Furthermore, we observed a 60% and 46% anxiety rates among the non-medical and medical students, respectively, in this study, which were higher than those reported in previous Saudi Arabian studies. 17 , 31 Recently, a meta-analysis reported global anxiety rates of 29.2%-38.7% among the medical students, with higher anxiety levels among the Asian and Middle Eastern students. 12 Several previous studies have demonstrated high stress levels among the medical, dental, and nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, we observed a 60% and 46% anxiety rates among the non-medical and medical students, respectively, in this study, which were higher than those reported in previous Saudi Arabian studies. 17 , 31 Recently, a meta-analysis reported global anxiety rates of 29.2%-38.7% among the medical students, with higher anxiety levels among the Asian and Middle Eastern students. 12 Several previous studies have demonstrated high stress levels among the medical, dental, and nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Similar to anxiety and depression, the level of stress among medical students, in the same region, was as high as 59%, and was more prevalent among female and junior students. 15,16 Several English scales have previously been used to assess the DASD prevalence in local population of Saudi Arabia, 7,13,17,18 and a number of local studies conducted on medical students exhibited certain methodological weaknesses, such as inadequate sampling. [19][20][21] Therefore, our aim was comparison of the DASD levels between medical and non-medical students with an adequate sampling method and by utilizing an Arabic validated tool that is more understandable in our culture, and to investigate risk factors for DASD among this population.…”
mentioning
confidence: 99%
“…Globally, the prevalence of anxiety among medical students is higher than that among the general population, which globally ranges from 29.2% to 38.7% and is 17% in KSA. [ 21 ] Medical students were determined to be more susceptible to academic stress owing to academic requirements. [ 16 22 23 ] High stress among medical students impairs the learning ability that may eventually affect the quality of patient care they provide after graduation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also reported a significant association between COVID-19 and anxiety level. [ 21 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, those in the age group (45 years and over) are more anxious than those in the two other age groups (25 years or less and 25 -less than 45 years. Farahat, 2019;Al-Abdi, 2019;Adas et al, 2019;Nevajda et al, 2019;Meng et al, 2019;Pandey et al, 2017;Ballan, 2014…”
mentioning
confidence: 99%